Pemanfaatan dan Peningkatan Produksi Rumput Laut bagi Masyarakat Desa Torokeku, Kecamatan Tinanggea, Konawe Selatan, Sultra - Fajriah Fajriah; Junaidin Junaidin; Iin Nudiyanti; Kobajashi T Isamu (Jurnal Pengabdian Pada Masyarakat, 2019)
UTILIZATION AND INCREASE OF SEAWEED PRODUCTION FOR THE COMMUNITY OF TOROKEKU VILLAGE TINANGGEA SUB-DISTRICT, KONAWE SELATAN, SOUTHEAST SULAWESI. Torokeku Village, Tinanggea Sub-District, South Konawe Regency is one of the villages that produce seaweed and various types of sea fish caught from Southeast Sulawesi. The problems faced by residents include: 1) Decreasing the amount of production and quality of seaweed, 2) Low level of entrepreneurial knowledge possessed, 3) lack of MSMEs as a single forum for independent business development for Torokeku Village residents. The specific goals and targets of the KKN-PPM: 1) Increasing the production and quality of seaweed seeds, 2) Increasing the skills of citizens in processing seaweed into various ready-to-eat and ready-to-cook products such as dodol, meatballs and seaweed nuggets, 3) Establishment and co-operative assistance for citizens. The methods used to achieve these goals are training, mentoring, lectures, discussions, direct visits, practices and demonstrations. The activities carried out included: (1) Making seaweed nursery gardens (2) Demonstration on various processed products ready to eat and ready to cook (dodol, meatballs and nuggets of seaweed), (3) Pioneering fishing cooperatives and UMKM, (4) Providing learning facilities for children and the community of Torokeku Village in the form of socializing education on the concept of sustainable fisheries as well as mentoring learning in schools and TPA.